Polygenic risk scores for neuropsychiatric, inflammatory, and cardio‐metabolic traits highlight possible genetic overlap with suicide attempt and treatment‐emergent suicidal ideation. Issue 3 (21st February 2022) - Fanelli, Giuseppe; Sokolowski, Marcus; Wasserman, Danuta; ,; Kasper, Siegfried; Zohar, Joseph; Souery, Daniel; Montgomery, Stuart; Albani, Diego; Forloni, Gianluigi; Ferentinos, Panagiotis; Rujescu, Dan; et al.
Abstract: Suicide is the second cause of death among youths. Genetics may contribute to suicidal phenotypes and their co‐occurrence in other neuropsychiatric and medical conditions. Our study aimed to investigate the association of polygenic risk scores (PRSs) for 24 neuropsychiatric, inflammatory, and cardio‐metabolic traits/diseases with suicide attempt (SA) or treatment‐worsening/emergent suicidal ideation (TWESI). PRSs were computed based on summary statistics of genome‐wide association studies. Regression analyses were performed between PRSs and SA or TWESI in four clinical cohorts. Results were then meta‐analyzed across samples, including a total of 688 patients with SA ( N eff  = 2, 258) and 214 with TWESI ( N eff  = 785). Stratified genetic covariance analyses were performed to investigate functionally cross‐phenotype PRS associations. After Bonferroni correction, PRS for major depressive disorder (MDD) was associated with SA (OR = 1.24; 95% CI = 1.11–1.38; p  = 1.73 × 10 −4 ). Nominal associations were shown between PRSs for coronary artery disease (CAD) ( p  = 4.6 × 10 −3 ), loneliness ( p  = .009), or chronic pain ( p  = .016) and SA, PRSs for MDD or CAD and TWESI ( p  = .043 and p  = .032, respectively). Genetic covariance between MDD and SA was shown in 86 gene sets related to drugs having antisuicidal effects. A higher genetic liability for MDD may underlie a higher SA risk. Further, but milder, possible modulatory factors are genetic risk for loneliness and CAD.